2005
DOI: 10.1186/1471-2407-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the XRCC1, XRCC3, & XPDgenes, and colorectal cancer risk: a case-control study in Taiwan

Abstract: Background: Recent studies relating to the association between DNA repair-gene polymorphisms and colorectal cancer risk would, to the best of our knowledge, appear to be very limited. This study was designed to examine the polymorphisms associated with three DNA repair genes, namely: XRCC1 Arg399Gln, XRCC3 Thr241Met and XPD Lys751Gln, and investigate their role as susceptibility markers for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
55
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 42 publications
15
55
7
Order By: Relevance
“…(95% CI=0.96-5.4). Our findings are in concordance with those reported by Mort et al (2003), Krupa et al (2011) andImporta et al (2008) and contradictory to those reported by many authors (Tranah et al, 2004;Stern et al, 2005;Yeh et al, 2005;Skjelbred et al, 2006) which show negative association. Also, it has been suggested that variant genotypes of XRCC3 have decreased repair capacity and thus individuals with this genotypes do not repair double strand DNA breaks efficiently by HRR and are susceptible to risk of CRC (Krupa et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…(95% CI=0.96-5.4). Our findings are in concordance with those reported by Mort et al (2003), Krupa et al (2011) andImporta et al (2008) and contradictory to those reported by many authors (Tranah et al, 2004;Stern et al, 2005;Yeh et al, 2005;Skjelbred et al, 2006) which show negative association. Also, it has been suggested that variant genotypes of XRCC3 have decreased repair capacity and thus individuals with this genotypes do not repair double strand DNA breaks efficiently by HRR and are susceptible to risk of CRC (Krupa et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…XRCC3 deficient HCT116 cells have shown increased sensitivity to cisplatin and mitomycin C (42). Although some studies have shown no association between polymorphisms in XRCC3 and colorectal cancer risk (43)(44)(45)(46) other studies have (47,48), and in addition XRCC3 polymorphisms have also been associated with breast and lung cancer susceptibility (41,49).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report a reduced risk of cancer associated with the 194Trp allele (Goode et al, 2002). The 399 polymorphism have been associated with a number of cancers, although results have been inconsistent (Abdel-Rahman et al, 2000;Goode et al, 2002;Mort et al, 2003;Nexo et al, 2003;Vogel et al, 2004;Hong et al, 2005;Yeh et al, 2005). Few studies have investigated the association between the XRCC1 280His allele and risk of cancer.…”
Section: Introductionmentioning
confidence: 99%